2020
DOI: 10.3389/fncel.2020.561857
|View full text |Cite
|
Sign up to set email alerts
|

Synaptojanin2 Mutation Causes Progressive High-frequency Hearing Loss in Mice

Abstract: Progressive hearing loss is very common in the human population but we know little about the underlying molecular mechanisms. Synaptojanin2 (Synj2) has been reported to be involved, as a mouse mutation led to a progressive increase in auditory thresholds with age. Synaptojanin2 is a phosphatidylinositol (PI) phosphatase that removes the five-position phosphates from phosphoinositides, such as PIP 2 and PIP 3 , and is a key enzyme in clathrin-mediated endocytosis. To investigate the mechanisms underlying progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…In SYNJ2 , we identified an association with a missense (Thr656Met) 18 variant that lies in the catalytic domain of this inositol polyphosphate 5-phosphatase 42 . Mice harboring homozygous mutations in Synj2 that are predicted to reduce protein levels or the 5-phosphatase catalytic activity show progressive high-frequency hearing loss and a degeneration of hair cells that is most profound in the outer hair cells 43,44 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In SYNJ2 , we identified an association with a missense (Thr656Met) 18 variant that lies in the catalytic domain of this inositol polyphosphate 5-phosphatase 42 . Mice harboring homozygous mutations in Synj2 that are predicted to reduce protein levels or the 5-phosphatase catalytic activity show progressive high-frequency hearing loss and a degeneration of hair cells that is most profound in the outer hair cells 43,44 .…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with the hypothesis from our genetic findings that loss of KLHDC7B function increases risk for hearing loss, initial characterization of Klhdc7B null mice by IMPC showed that homozygous carriers have hearing loss 26 . Mouse models Fscn2 and Synj2 also develop hearing loss 41,43,44 . Based on our association results, it would also be interesting to test heterozygous null Klhdc7b, Fscn2 , and Synj2 animals for increased susceptibility to hearing loss with age or environmental insults such as noise-exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mozart mice also exhibit stereociliar fusion, loss of hair cell bundles, and subsequent hair cell degeneration [44]. A second study on mice with a different Synj2 mutation in the phosphatase catalytic domain was able to confirm the observation of progressive hearing loss in Synj2-deficient mice [114].…”
Section: Co-staining Of Synaptojanin 2 (Ch) and Matrix Metalloproteinase 2 (Mmp2)mentioning
confidence: 88%
“…IHC = inner hair cell, OHCs = outer hair cells, Pv = Parvalbumin, cut. = cuticula, TJ = tight junction, SC = stereocilia, Ph = phalangeal cell, r = stereociliar rootlet inner hair cells [44] as well as the spiral ganglion [114] (Fig. 5C).…”
Section: Co-staining Of Synaptojanin 2 (Ch) and Matrix Metalloproteinase 2 (Mmp2)mentioning
confidence: 99%